Psychotherapy in the Third Reich : the Göring Institute - Cocks, Geoffrey 1948- (Transaction Publ, 1997)
Much research has been done in the ten years since the first edition of this book was published, hence the need for a second edition. Included is more information on the history of psychotherapy and psychoanalsis, in Nazi Germany, on the social history of the Third Reich, and on the history of the professions in Germany. Three new chapters analyze postwar developments and conflicts as well as broader issues of continuity and discontinuity in the history of modern Germany and the West. In addition, the author has recognized the volume along chronological and narrative lines for greater ease of reading. Psychotherapy in the Third Reich is an important work for psychotherapists, psychologists, psychoanalysts, sociologists, and historians